INVESTIGATING THE IMPLICATIONS OF DC DISTRIBUTION NETWORKS ON RENEWABLE ENERGY INTEGRATION AND FLEXIBLE ENERGY STORAGE EFFICIENCY (Jurnal Teknologi (Sciences & Engineering), 2025)
This research examines the impact of DC distribution networks on integrating renewable energy sources and the effectiveness of flexible energy storage systems in enhancing network efficiency. The study evaluates the performance, stability, and potential of DC distribution networks as key enablers for achieving a sustainable and reliable energy system. The analysis focuses on the potential benefits and challenges associated with integrating renewable energy sources into DC distribution networks. It investigates how these networks efficiently manage and utilize renewable energy, addressing issues such as voltage regulation, power quality, and system stability. Additionally, the research explores the role of flexible energy storage technologies in mitigating the intermittency of renewable energy sources. It evaluates the effectiveness of energy storage systems, including batteries, pumped hydro storage, and compressed air energy storage, optimizing network stability, improving energy dispatch ability, and maximizing renewable energy utilization. An economic analysis assesses the viability and cost-effectiveness of implementing DC distribution networks with renewable energy integration and flexible energy storage. This analysis considers investment costs, operational expenses, and potential revenue streams, providing insights for decision-makers and energy planners. They inform policymakers, system operators, and energy industry stakeholders, facilitating informed decision-making and the development of strategies to optimize energy system efficiency, reliability, and sustainability. In conclusion, this research provides a comprehensive assessment of the implications of DC distribution networks on renewable energy integration and flexible energy storage efficiency. The insights gained significantly impact achieving a more sustainable and resilient energy future.